Request to speed up the payment process of interim payment application no. 023 (part-B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding request to speed up the payment process of interim payment application no. 023 (part-B) of BRAC University new campus project.